THERAPEUTIC-DIAGNOSTIC ALGORITHM IN DIFFERENT PHENOTYPES OF POLYPOUS RHINOSINUSITIS - Durdona D. Alimova (Central Asian Journal of Medicine, 2023)
In recent years, there has been a noticeable increase in the proportion of rhinosinusitis polyps in the structure of nasal cavity and paranasal sinus diseases, which is due to a number of factors: changes in environmental conditions, an increase in the number of bacterial, viral, and professional pathogenic agents. The use of combined treatment regimens using topical and systemic corticosteroids has shown promising results, but requires further standardization in terms of drug selection, duration of administration, and safety monitoring. The aim of this study was to improve the methods of diagnosis and treatment of patients with polypous rhinosinusitis.